Higher Education Completion Rates for Aboriginal and Torres Strait Islander Students Using A Multi-Agency Matched Population Cohort - Ladbrook, Megan; Hendrickson, Luke (International Journal of Population Data Science, 2020)
Using the Multi-Agency Data Integration Project (MADIP), which combines health, tax, welfare and demographic data with student data, our analysis looked at the relationship between income support and Aboriginal and Torres Strait Islander university completion rates. Introduction Domestic undergraduate university completion rates of Aboriginal and Torres Strait Islander students are significantly lower (40%) than non-Indigenous students (66%). Few prior studies have used population level matched data from multiple agencies to analyse the determinants of Australian Indigenous completion rates. Objectives and Approach We aimed to quantify the major determinants driving the completion rates of Indigenous students in Australian undergraduate university courses compared with domestic non-Indigenous students. We used the Higher Education Information Management System (HEIMS) linked to the MADIP creating approximately 555, 000 records. A Random forest tree was constructed to determine the most important indicators for outcome of interest which were then used for matching and statistical analysis. Summary statistics and a binomial logit was used on the matched sample to confirm significance. Results We found that Indigenous students are more likely to start university belonging to around three equity groups such as having a lower socio-economic status background, older commencement age and being the first member of their family to attend university. However, Indigenous status remains a significant contributor to lower completion rates after controlling for a wide range of equity groups. One factor that has a positive influence on Indigenous university completion rates is access to study assistance. Completion rates for Indigenous students who were not members of other equity groups on income support was 70 per cent compared to 57 per cent for similar students on no income support. Conclusion / Implications These linked datasets provide the opportunity to better evaluate the drivers of completion rates of Australian Indigenous students to inform and evaluate policy reforms.